中国农村经济改革研究 = The study of economic reform in rural China - 丁莉莉 Ding, Lili (2008)
This paper studies the problems facing the reform of taxation and charge system in rural China, addresses the current situation and the characteristics of farmers' burden, analyzes the fundamental reasons of farmers' heavy burden, points out the difficulties in reforming the taxation and charge system in rural China.